2010
DOI: 10.3892/ijo_00000583
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus infection induces apoptosis of TRAIL-resistant gastric cancer cells by down-regulation of Akt activation

Abstract: Abstract. The tumor necrosis factor (TNF)-related apoptosisinducing ligand (TRAIL) has been used to treat a variety of cancer cells. However, since some gastric cancer cells are resistant to TRAIL, we explored whether reovirus induces cytolysis in TRAIL-resistant gastric cancer cells. We found that TRAIL-resistant SNU-216 gastric cancer cells were susceptible to apoptosis by reovirus infection. Furthermore, co-treatment with reovirus and TRAIL accelerated apoptosis of SNU-216 cells by down-regulation of Akt ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…The mean volume of ascites and total number and weight of peritoneal tumors also decreased in reovirus-treated mice (Table 3). Meanwhile, Cho et al showed that reovirus downregulates the activation of Akt, a protein kinase that drives oncogenesis, and signaling molecules that promote cell proliferation and survival, including Ras and ERK (Table 3) [130]. Reovirus induced the apoptosis of TRAIL-resistant GC cells via these mechanisms.…”
Section: Reovirusmentioning
confidence: 99%
“…The mean volume of ascites and total number and weight of peritoneal tumors also decreased in reovirus-treated mice (Table 3). Meanwhile, Cho et al showed that reovirus downregulates the activation of Akt, a protein kinase that drives oncogenesis, and signaling molecules that promote cell proliferation and survival, including Ras and ERK (Table 3) [130]. Reovirus induced the apoptosis of TRAIL-resistant GC cells via these mechanisms.…”
Section: Reovirusmentioning
confidence: 99%
“…The exact mechanism of MRV reduction in HIF-1 accumulation is not known. However, MRV inhibits the accumulation of HIF-1 independently of the oxygen-dependent pathway in a manner dependent on RACK1 and ubiquitin-mediated proteasomal degradation [32,37]. Moreover, a step between viral capsid cleavage and transcription of viral mRNA during the MRV life cycle has been found to be sufficient to induce the MRV effect on HIF-1 accumulation [34].…”
Section: Mammalian Orthoreovirus (Mrv) Is a Clinically Benign Oncolyt...mentioning
confidence: 99%
“…Apoptosis by reovirus appears to require IRF-3 and NF-κB, in part, for efficient expression of the pro-apoptotic member of the Bcl-2 family, Noxa, independent of IFN-β induction (34). Reovirus appears to downregulate cellular FLICE inhibitory protein (cFLIP) and Akt activation to increase susceptibility to TRAIL-induced apoptosis in ovarian cancer cells and gastric cancer cells, respectively (59, 60). In neurons, reovirus-induced apoptosis is facilitated by upregulation of death-associated protein 6 (Daxx), an adaptor between the Fas death receptor and JNK signaling cascade, within the cytoplasm (61, 62).…”
Section: Mechanism Of Oncolysismentioning
confidence: 99%